Legislative activity of the Icelandic bishopric in the second half of the XI - first half of the XII century. - Kravchenko, I. O. (Ukrai͏̈ns'ke relihijeznavstvo, 2008)
A number of scholars in the history of medieval Iceland have emphasized the exceptional importance of law and justice for Icelandic society. According to American researcher J. Bajok, the focus of Iceland's culture was law, and the relationship between Godi and his heirs was also based on law. The nature of Iceland's socio-political institutions reveals the circumstances in which Icelanders' attitudes towards the law were shaped. The royal power in the country during the Commonwealth period did not arise, and the system of chiefs or Godords became specifically the Icelandic institute of government. It is traditionally believed that the country was divided into 4 quarters, consisting of 36 (later 39) Godords, headed by leaders (mn. Goarar). The year 930 is considered the date of Altinga's founding. National Assembly of Iceland. Each year, a three-year lawmaker in Altinga had to promulgate a third of the country's laws. The lawmaker selected those who were to sit on the Rock of Law and designate the place where the Courts of the Quarters, which had pending lawsuits, were to be held. The most important institution of Altinga was the Legislative Council, which dealt with legal issues. The council members were 48 leaders or heads. The representatives of the highest level of the religious hierarchy - the bishops of dioceses on the Chamber Hill (Skullholt) and the Hills (Holar) - were also members of the Legislative Council. The bishops participated in three important events for the country: the drafting and adoption of the Law of Tithes in 1096/97, the codification of secular laws in 1117 - 1118, and the record of about 1123 of the Christian Law, which was included in the Gray Law Code. Goose ", probably recorded in the XIII century.